2013
DOI: 10.1111/idh.12048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wearing loupes on upper extremity musculoskeletal disorders among dental hygienists

Abstract: Overall, this study suggests that wearing loupes appears to have both positive and negative effects on upper extremity MSD among dental hygienists. Ongoing research is required to determine the long-term effects of loupes wear, over an extended period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 33 publications
1
57
0
2
Order By: Relevance
“…4 This study found that the ergonomic scores improved for students in the control group, based on self-assessments, and students in the training group, based on rater scores. Overall, the use of a convenience sample of students functioned well for this pilot study.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…4 This study found that the ergonomic scores improved for students in the control group, based on self-assessments, and students in the training group, based on rater scores. Overall, the use of a convenience sample of students functioned well for this pilot study.…”
Section: Discussionmentioning
confidence: 72%
“…[1][2][3][4][5][6][7][8][9][10][11] Among one group of dentists, 73.9% of respondents reported musculoskeletal pain, even though 59.3% reported an awareness of neutral ergonomic positions. [1][2][3][4][5][6][7][8][9][10][11] Among one group of dentists, 73.9% of respondents reported musculoskeletal pain, even though 59.3% reported an awareness of neutral ergonomic positions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This range is alarming but corroborates similar studies with dentists. 12,14,21,22 Ergonomic aspects are not subject of this study, but it should be mentioned that this positive effect is dependent on a good adjustment with respect to the individual working position. The better near visual performance of the younger group could be expected owing to the presbyopic constraints above an age of 40 years.…”
Section: Discussionmentioning
confidence: 97%
“…Most dentists and dental hygienists that use loupes are convinced that their magnification devices and a good near visual acuity have an impact on the treatment outcome, although the scientific evidence in this field is still weak. [12][13][14][15] To the best of our knowledge, no studies about the near visual performance of dental hygienists have been published so far. 9,10 Visual deficiencies can be compensated for with magnification aids in a standardized setting as well as in the individualized setting of a private practice.…”
Section: Introductionmentioning
confidence: 99%